Relationship Workloads with Work Satisfactionlabor Contract on The Tomkins Shoes Company - R. Rina Novianty Ariawaty; Siti Noni Evita (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
In facing global market competition, every company has different production standards. To meet work targets, the company imposes work on both low and high workloads. The workload was allegedly able to affect the satisfaction felt by the workforce. This study aims to determine the relationship of workload with contract labor satisfaction. The method used in this research uses the descriptive method by taking a sample of 86 contract workers. Analyze the correlation between variables, namely workload and job satisfaction, using the Spearman Rank Correlation formula. The results of this study indicate that there is a relationship between workload and job satisfaction of contract workers found that there is a relationship with a percentage of 21.6%.